Inhibition of RNA synthesis during Scriptaid exposure enhances gene reprogramming in SCNT embryos. Issue 2 (February 2019) - Rissi, Vitor Braga; Glanzner, Werner Giehl; de Macedo, Mariana Priotto; Mujica, Lady Katerine Serrano; Campagnolo, Karine; Gutierrez, Karina; Bridi, Alessandra; Baldassarre, Hernan; Gonçalves, Paulo Bayard Dias; Bordignon, Vilceu
Abstract : Insufficient epigenetic reprogramming is incompatible with normal development of embryos produced by somatic cell nuclear transfer (SCNT), but treatment with histone deacetylases inhibitors (HDACi) enhances development of SCNT embryos. However, the mechanisms underpinning HDACi benefits in SCNT embryos remain largely uncharacterized. We hypothesized that, in addition to enhancing reprogramming, HDACi treatment may promote expression of genes not required for early development of SCNT embryos. To test this hypothesis, RNA synthesis was inhibited by treating bovine SCNT embryos with 5, 6-dichlorobenzimidazole 1-β-D-ribofuranoside (DBR), which were concomitantly treated or not with Scriptaid (Scrip; an HDACi). Development to the blastocyst stage was significantly increased by treatment with Scrip alone (26.6%) or associated with DRB (28.6%) compared to Control (17.9%). The total number of nuclei was significantly improved only in embryos that were treated with both Scrip + DRB. Nuclear decondensation after SCNT was significantly increased by DRB treatment either alone or associated with Scrip. The relative mRNA expression, evaluated during the embryo genome activation (EGA) transition, revealed that some KDMs ( KDM1A, KDM3A, KDM4C and KDM6A ) and DNMT1 where prematurely expressed in Scrip-treated embryos. However, treatment with Scrip + DRB inhibited early mRNA expression of those genes, as well as several other KDMs ( KDM4A, KDM4B, KDM5A, KDM5B, KDM5C and KDM7A ) compared to embryos treated with Scrip alone. These findings revealed that HDACi improved development in SCNT embryos compared to Control, but altered the expression of genes involved in epigenetic regulation and did not improve embryo quality. Inhibition of RNA synthesis during HDACi treatment enhanced nuclear chromatin decondensation, modulated gene expression and improved SCNT embryo quality.